Membrane Proteins Involved in Epithelial-Mesenchymal Transition and Tumor Invasion: Studies on TMPRSS4 and TM4SF5 - Semi Kim; Jung Weon Lee (Genomics & Informatics)
The epithelial-mesenchymal transition (EMT) is one mechanism by which cells with mesenchymal features can be generated and is a fundamental event in morphogenesis. Recently, invasion and metastasis of cancer cells from the primary tumor are now thought to be initiated by the developmental process termed the EMT, whereby epithelial cells lose cell polarity and cell-cell interactions, and gain mesenchymal phenotypes with increased migratory and invasive properties. The EMT is believed to be an important step in metastasis and is implicated in cancer progression, although the influence of the EMT in clinical specimens has been debated. This review presents the recent results of two cell surface proteins, the functions and underlying mechanisms of which have recently begun to be demonstrated, as novel regulators of the molecular networks that induce the EMT and cancer progression.